Social determinants of Chagas disease in Costa Rica - Ramirez Solano, Ana Maria (2023)
Introduction: Among the main diseases associated with the social determinants of health, lifestyles and healthy environments, is Chagas disease, which is linked to poverty and infrastructures whose conditions promote the permanence of the vector. Therefore, the objective of this article was to carry out an exploratory ecological analysis of the social determinants of health related to the prevention and control of Chagas disease, for the generation of relevant epidemiological knowledge and the formulation of public policy guidelines, which help to improve the approach to this public health problem and fulfill the national commitment to eliminate this neglected disease. Methodology: an ecological and geographical study was designed considering social determinants to the prevention and the regulation of the Chagas disease. To this end, this study is based on primary data by the Ministerio de Salud (MINSA) and the Instituto de Estadística y Censos (INEC), the information was analyzed by generating maps using GIS, in addition to a negative binomial linear regression and a spatial neighborhood analysis by calculating the Moran Index. Results: From the sample analyzes, it can be drawn that the most influential factors regarding the contagion rate for Chagas disease are the percentage of canton-level urban slums, the percentage of poor homes, and the percentage goods and services missing. Conclusions: The results obtained imply a relationship between Chagas disease and the social determinants of health, especially linked to inequity and inequality, which is why this document proposes public policy guidelines that allow the recording of information related to social determinants of health. that facilitate the surveillance of the disease and that lead to the identification or elimination of a possible underreporting of cases derived from the lack of analysis of indicators of social determinants of health.